2008
DOI: 10.1021/jf072822m
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Property of Endosperm Starches from Maize Mutants: A Parabolic Relationship between Slowly Digestible Starch and Amylopectin Fine Structure

Abstract: The relationship between the slow digestion property of cooked maize starch and its molecular fine structure was investigated. Results of the in vitro Englyst assay showed a range of rapidly digestible starch (RDS) (70.1-98.9%), slowly digestible starch (SDS) (0.2-20.3%), and resistant starch (RS) (0.0-13.7%) among the tested maize mutant flour samples. Further analysis showed that amylose content was significantly correlated ( R = 0.763, P < 0.001) with RS amount but not with that of SDS, indicating that amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(114 citation statements)
references
References 42 publications
9
94
1
Order By: Relevance
“…Our in vitro starch digestibility results corroborate those of Zhang et al [16] in waxy maize, wheat, rice and maize starches. The RDS, SDS and RS levels of the parkia starches cannot be compared with those reported for other legume starches, due to differences in methods used and different duration of hydrolysis that were used for determination of RDS, SDS and RS levels.…”
Section: Discussionsupporting
confidence: 91%
“…Our in vitro starch digestibility results corroborate those of Zhang et al [16] in waxy maize, wheat, rice and maize starches. The RDS, SDS and RS levels of the parkia starches cannot be compared with those reported for other legume starches, due to differences in methods used and different duration of hydrolysis that were used for determination of RDS, SDS and RS levels.…”
Section: Discussionsupporting
confidence: 91%
“…This trend would only be significant in extruded matrices compared with the native ones, being the later less prone to mild hydrothermal reorganizations as a consequence of their packed morphology. It is important to point out that amylose is the main starch molecule related to RS [35]. Martínez et al [12] reported an increase in the amylose content during the branching enzyme treatments.…”
Section: Resistant Starch Contentmentioning
confidence: 99%
“…However, Han et al [34] indicated that short chains of amylopectin and amylose were preferentially digested (rapidly), while DP 121 chains were resistant to amylase hydrolysis, followed by those of DP 46. Furthermore, Zhang et al [35,36] found that maize starches with either longer or shorter branches showed slower digestion properties based on: 1) the potential of long branches to form crystallites and, 2) the presence of a highly branched amorphous lamella, entailing a higher content in short chains, that halt the rearrangement of the crystalline double helices in amylopectin. In this way, Bertoft et al [37] recently hypothesized that even those nuances in the structural architecture can have a pronounced effect on the properties of starch.…”
Section: Starch Hydrolysis Kineticsmentioning
confidence: 99%
“…High amylose starches are correlated with a type of resistant starch (RS). [62] RS is not digested in the small intestine and instead reaches the large intestine, where it is fermented to produce short-chain fatty acids, which have a role in maintaining bowel health and can assist in the prevention and treatment of colonic disease. [63,64] The starch gelatinization temperature (GT) is an important trait affecting the rate of the processes required to drive the transition from flour to gel (e.g.…”
Section: Techniques and Assumptionsmentioning
confidence: 99%